Ophthalmic Parameters of Healthy White-Eyed Parakeets (Psittacara leucophthalmus) - Pigatto, Anita Marchionatti [UNESP]; Brandão, Cláudia Valéria Seullner [UNESP]; Rahal, Sheila Canavese [UNESP]; Cassanego, Guilherme Rech [UNESP]; Peixoto, Gabriella De Nardin [UNESP]; Santos, José Gabriel Calhari [UNESP]; Tokashiki, Erick Yuji [UNESP]; Padovani, Carlos Roberto [UNESP] (My University, 2025)
White-eyed parakeets (Psittacara leucophthalmus) are medium-sized birds that are diurnal and arboreal and eat a predominantly fruit-based diet. Although white-eyed parakeets are frequently presented with ocular lesions, information about ophthalmological parameters for this species is limited. Therefore, this study aimed to characterize the baseline ophthalmic parameters of healthy, white-eyed parakeets to contribute to a better understanding of their ocular health. This study evaluated the modified Schirmer tear test I (mSTTI), standardized endodontic absorbent paper point tear test (EAPPTT), intraocular pressure (IOP), central corneal thickness (CCT), and measurement of the palpebral fissure length (PFL) of 24 adult white-eyed parakeets under manual restraint. The same evaluator examined both eyes of each bird. To avoid any interference for the tear tests, 12 birds were assigned to mSTTI and 12 to EAPPTT. There was a significant difference (P = 0.031) in the PFL between eyes, with right eyes measuring 7-9 mm and left eyes 6-8 mm. There was no significant difference (P = 0.435) in CCT between eyes. There was a significant difference (P < 0.001) between the mSTTI and EAPPTT values, with EAPPTT values being higher than mSTTI values. There was no significant difference (P = 0.157) for these measures within bird. There was a significant difference (P < 0.001) in the IOP values between the different species parameters, with significant differences (all P <0.001) recorded between all species measures except dog and rabbit (P = 0.09). There was no significant difference (P = 0.157) for the IOP measures within bird. The ophthalmic parameters obtained from the adult, white-eyed parakeets in this study can be used to expand our knowledge about the species and help distinguish healthy eyes from diseased eyes.
Keywords: avian; eye; ophthalmic; Psittacara leucophthalmus; psittacine; white-eyed parakeet